AREPO-RT: radiation hydrodynamics on a moving mesh - Kannan, Rahul; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We introduce arepo-rt, a novel radiation hydrodynamic (RHD) solver for the unstructured moving-mesh code arepo. Our method solves the moment-based ra